Output, Employment and Financial Sanctions in South Africa - Bayoumi, Tamim (IMF Working Papers; Working Paper, 1990)
The effects of the marked slowdown in the growth of the capital stock in South Africa since 1985, associated with political uncertainty and financial sanctions, and future growth prospects are quantified using a modified version of the Lewis development model. This is done by estimating production functions for the nonprimary and mining sectors of the South African economy involving skilled (white) labor, unskilled (nonwhite) labor and capital. It is concluded that each 1 percent change in the growth rata of the capital stock leads to at 0.8 percent change in output growth, and hence the fall in investment since 1985 has lead to significant falls in growth, employment and real wages.